Hypoparathyroidism: Early Detection and Diagnosis Approaches - Rizqina Alya Shafa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Hypoparathyroidism is an endocrine disorder characterized by low or absent production of parathyroid hormone (PTH). The most common cause of hypoparathyroidism is injury to the parathyroid glands or unintentional removal during thyroid surgery. The author aims to explore further the early detection and diagnostic approaches for hypoparathyroidism. The search was conducted through the Pubmed database using the keywords